1998
DOI: 10.1017/s0265051700003788
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Strategies in Computer-Based Music-Making

Abstract: Recent technological developments and the increasing impact of the media mean that listening to music and creative music making constitutes a major and integrated part of many young people's lives.The aim of the present article is to describe the process of computer-based composition, and how this is perceived by young composers. This paper describes a three-year empirical study of 129 computer-based compositions by 15 to 16-year-olds. Computer MIDI-fti.es were systematically collected covering the sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 5 publications
(3 reference statements)
0
43
0
1
Order By: Relevance
“…Gardner (1982) is also intrigued by similarities in the learning of songs with other domains such as language and drawing. Patterns may be important when composing with computer-based sequencing programmes where the shapes or blocks of music can be manipulated with reference to an on-screen visual representation of the musical material (Folkestad, 1998;Folkestad, Hargreaves & Lindstrom, 1998). In that way, thinking about composition involves other domains which can enrich understanding in music, in those other domains and in the relationships between them.…”
Section: Critical Thinking In Musicmentioning
confidence: 99%
“…Gardner (1982) is also intrigued by similarities in the learning of songs with other domains such as language and drawing. Patterns may be important when composing with computer-based sequencing programmes where the shapes or blocks of music can be manipulated with reference to an on-screen visual representation of the musical material (Folkestad, 1998;Folkestad, Hargreaves & Lindstrom, 1998). In that way, thinking about composition involves other domains which can enrich understanding in music, in those other domains and in the relationships between them.…”
Section: Critical Thinking In Musicmentioning
confidence: 99%
“…This paper argues that if we remove children from an environment in which their creative, expressive and musical choices are constrained by the instruments, the environment itself, (Amabile and Gitomer, 1984;Kratus, 2001) and their skills, then what occurs when we place them in a new environment will be richer. The restriction now is placed on "the potential of the computer" (Folkestad et al, 1998) rather than on the musical ability of the child.…”
Section: Resultsmentioning
confidence: 99%
“…The children are encouraged to throw nothing away, even the files they no longer wish to use. I do not believe it necessary or practical to collect every saved version of every alteration to a file (Folkestad et al, 1998), the analysis of what the children produce each session should be adequate. In this way computers can aid the process of examination of the "history of a particular composition as displayed in the composer's written manuscripts" (Sloboda, 1985: 102).…”
Section: Computer As Data Collectormentioning
confidence: 99%
“…However, it would be hard to define an appropriate level of abstraction at which to make the comparison: we would not expect the compositions themselves to be the same at the note level. However, a number of studies have demonstrated broad strategic differences between composers (Folkestad et al, 1990) and related such differences to degrees of compositional expertise (Colley et al, 1992;Davidson & Welsh, 1988). A basis for the comparison of cognitive models with human data might be found at this level of general strategy.…”
Section: Discussionmentioning
confidence: 99%